Tari Inai Bagi Status Sosial Masyarakat Pengguna dalam Kegiatan Malam Berinai di Kec.Nipah Panjang - Shinta Jayanti; Indrayuda Indrayuda (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The article is the result of research aimed at describing and analyzing the relationship between Henna Dance and the Social Status of the User Community and the Role of Inai Dance in Current Berinai Night Activities. This type of research is qualitative research with descriptive methods. The research instrument is the researcher himself and is assisted by supporting instruments such as writing equipment and a camera. The data in this research uses primary data and secondary data. Data was collected through literature study, observation, interviews and documentation. The steps for analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the Henna Dance functions to protect the bride and groom from disturbances originating from humans and other creatures and as a blessing for the bride and groom who will live a new life. Apart from that, the Henna Dance or Berinai Night is called a night to introduce the groom to the entire extended family of the bride. However, currently the Inai Dance or Malam Berinai is rarely performed by the people of Nipah Panjang District, especially the Malay ethnic community in Nipah Panjang District. This is because the Henai Dance or Berinai Night event can only be performed by people whose economic class is relatively good. So currently it is very rare for researchers to see the Inai Dance or Malam Berinai culture in Nipah Panjang District.